The Development of Android-based Score Sheet Application for the Referee (Chair Umpire) in Tennis Match - Shodikin, Shodikin; Pramono, Harry; Rumini, Rumini (Journal of Physical Education and Sports, 2019)
This research is done based on problems that occur in tennis match because they still use manual Score Sheet, so researches interested in conducting research and development of an Android-based score sheet application for the referee (chair umpire). Development being done are the potential and problems, data collection, product design, design validation, design revision, free trial product, free trial usage. Data analysis using a quantitative and qualitative approach. The result of the research on the small scale product validation by tennis referee experts has obtained an average score of 4.5 with category of Ã¢â‚¬Å“very goodÃ¢â‚¬Â and IT experts obtained an average score of 4.2 with category of Ã¢â‚¬Å“good.Ã¢â‚¬Â While on the validation of large scale product by referees was 4.8 with the category of Ã¢â‚¬Å“very goodÃ¢â‚¬Â and IT experts obtained an average score of 4.7 with the category of Ã¢â‚¬Å“very good.Ã¢â‚¬Â The final product effectiveness test on a small scale trial was stated Ã¢â‚¬Å“very goodÃ¢â‚¬Â with a percentage of 81.72 % by the referee. While on the large scale trial obtained a percentage of 93.44% by the referee. The conclusions of this research were product development of Android-based score sheet application at tennis match greatly helped the refereeÃ¢â‚¬â„¢s performance in recording match statistics, Product development of Android-based score sheet application for the referee at tennis match was worthy of being used as mass products.